Do We Count?. Issue 5 (September 2016) - Capron, Alexander M.
Abstract: In the article "A Conceptual Model for the Translation of Bioethics Research and Scholarship, " Debra Mathews and her colleagues want to apply to bioethics various translational concepts developed for biomedical research. According to experts in translational science, this would mean evaluating not only the extent to which research produces the "changes in thinking, practice, and policy" that interest Mathews et al. but also the appropriateness of bioethics training and the level of competency of people working in the field. Their proposal thus raises two sets of questions. The first, which the authors recognize must be the starting point for their argument, is, what precisely is the field in question? The second is whether the tools of translational science provide the right means of measuring the achievements of bioethics .